IT Governance through Mathematical Modeling: A Quantitative Assessment of Maturity Using Factor Analysis and Structural Equation Modeling - Indrajit, Richardus Eko; Dazki, Erick; Kurniawan, Rido Dwi; Dio F, Januponsa (Informatika, Universitas Jenderal Soedirman, 2025)
IT Governance (ITG) ensures an organization's technological capabilities align with its business strategy. Although frameworks like COBIT 2019 offer structured guidelines, many assessment techniques rely on qualitative measures, which can compromise objectivity. This paper proposes a novel quantitative approach that integrates Factor Analysis (FA) and Structural Equation Modeling (SEM) to measure IT Governance maturity. By mapping each COBIT 2019 domain—EDM, APO, BAI, DSS, and MEA—onto a latent construct, organizations gain empirical insights into their governance status. Exploratory and confirmatory factor analyses validate these domains, while SEM reveals the magnitude and significance of each domain's impact on overall IT Governance maturity. A real-world example from a financial services company,